Anemia and Bone Marrow Suppression After Intra-Arterial Chemotherapy in Children With Retinoblastoma: A prospective Analysis - Nabi, Siraj; Ayaz, Muhammad; Malik, Pervaiz Azam; Payal, FNU; Ahmed, Nisar; Yasir Arafat, Muhammad; Ibrahim Rasool, Mohammad (Journal of Neonatal Surgery, 2025)
Background : To assess the incidence and severity of anemia and bone marrow suppression following intra-arterial chemotherapy in children diagnosed with retinoblastoma. Methods:This prospective study was conducted from May 2023 to May 2024 at People's University of Medical and Health Sciences Nawabshah, enrolling 77 children with confirmed retinoblastoma who underwent IAC. Hematological indices including hemoglobin, white blood cell count, absolute neutrophil count, and platelet levels were recorded before and after each chemotherapy cycle. Adverse events were graded using CTCAE criteria. Statistical analysis was performed using SPSS version 25, with p < 0.05 considered significant. Results: Post-treatment anemia was observed in 66.2% of patients, with 16.9% developing Grade 3–4 severity. Bone marrow suppression occurred in 49.4% of cases, with significant declines in hemoglobin (p < 0.001), WBC (p = 0.003), and platelet counts (p < 0.001). Blood transfusions were required in 28.6% of children. Treatment delays due to hematologic toxicity were noted in 15.6% of cases. Conclusion: Although IAC is localized in administration, its systemic hematologic effects are clinically significant. Regular blood count monitoring and timely supportive interventions are essential to mitigate the risks of anemia and marrow suppression in pediatric retinoblastoma patients undergoing this therapy.